The Effect of TPS vs NHT Teaching Methods on Math Learning Outcomes and Motivation - Budi Wahjuningsih; Achmad Noor Fatirul; Djoko Adi Walujo (Acitya: Journal of Teaching and Education, 2023)
This quasi-experimental study investigated the impact of the Think-Pair-Share (TPS) and Numbered Heads Together (NHT) teaching methods on mathematics learning outcomes and student motivation at SMKN 2 Kota Madiun and SMKN 5 Kota Madiun. The results showed that the experimental groups taught using the TPS method achieved significantly higher mathematics learning outcomes compared to the control groups taught using the NHT method (F = 18.522, p < 0.001). Additionally, students with high learning motivation demonstrated better academic performance than those with low motivation (F = 100.93, p < 0.001). An interaction effect was observed between the teaching method and learning motivation, indicating that the combination of teaching method and motivation significantly influenced mathematics learning outcomes (F = 4.294, p = 0.040). These findings highlight the effectiveness of the TPS method in improving mathematics learning outcomes and emphasize the importance of considering student motivation in instructional design. Further research is needed to explore the long-term effects of these teaching methods in different educational contexts and student populations, providing valuable insights into enhancing mathematics education.